2020
DOI: 10.1186/s13048-019-0606-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplets in granulosa cells are correlated with reduced pregnancy rates

Abstract: Background: Lipids are an important source for energy production during oocyte maturation. The accumulation of intracellular lipids binds to proteins to form lipid droplets. This may lead to cellular lipotoxicity. The impact of lipotoxicity on cumulus and granulosa cells has been reported. This pilot study evaluated their correlation to oocyte and embryo quality. Design: Prospective case-control study. Setting: Referral IVF unit. Patients: Women younger than age 40, undergoing IVF with intracytoplasmic sperm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
0
21
0
1
Order By: Relevance
“…This is also supported by the observation of morphological changes in OA treated GCs showing lipid droplet accumulation. Also in human lipid droplet accumulation in GCs have been correlated with fertility problems [ 24 ]. Also recent in vivo data suggest that increased NEFA levels and in particular increased OA concentrations in the follicular fluid have detrimental effects on follicle growth and even prevent ovulation [ 18 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is also supported by the observation of morphological changes in OA treated GCs showing lipid droplet accumulation. Also in human lipid droplet accumulation in GCs have been correlated with fertility problems [ 24 ]. Also recent in vivo data suggest that increased NEFA levels and in particular increased OA concentrations in the follicular fluid have detrimental effects on follicle growth and even prevent ovulation [ 18 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mediating the uptake of LDL by ovarian follicle cells, LDLR was downregulated in PCOS granulosa cells, which is consistent with previous studies ( 37 , 38 ). In addition, lipid content in granulosa and cumulus cells may affect likelihood of pregnancy, loss of function of LDLR resulted in impaired lipid uptake and extracellular lipid accumulation, thus leading to hyperlipidemia and poor fertility in mice ( 39 ). Overall, our results showed that abnormal lipid metabolism and fatty acid synthetic pathways were closely related to the development of PCOS, while the specific mechanism underlying how these metabolic disorders contributed to ovulatory disorders in PCOS remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study found that the patients with accumulation of lipid droplets in cumulus and granulosa cells had lower IVF/ICSI pregnancy rates, regardless of their BMI (Raviv et al, 2020). Excess fatty acids could damage the cumulus and granulosa cells, which are the major functional cells of the female gonads thus impairing their ability to perform normal steroidogenesis (Raviv et al, 2020). High dietary fat intake, with or without the development of obesity, impairs female hypothalamic-pituitary-ovarian (HPO) axis as well as fertility (Hohos and Skaznik-Wikiel, 2017).…”
Section: Discussionmentioning
confidence: 99%